Análise do processo de gestão do conhecimento na empresa Cerâmica Salema - Silva, Narjara Bárbara Xavier (2015)
This research studies the importance of knowledge management in a company in the industrial sector of the construction, considering the competitive and ever-expanding market. It is believed that the Knowledge Management (KM) can contribute, at first, with the productivity and competitiveness in organizational business and, as a consequence, stimulate social and economic development of the country. The overall objective is to analyze the process of knowledge management in Cerâmica Salema company, in view of Information Science. As specific objectives, we sought to identify existing practices in every step of the GC, they are: creation/acquisition; explicitness, filing and access; sharing/dissemination; editing/adaptation and disposal. In the methodological aspect, the research used the inductive method, being identified as an applied, exploratory and descriptive research with quantiqualitative approach. The research universe is composed of the members that make up the three organizational levels of Cerâmica Salema. As for the data collection procedures, it is a literature and field, whose instrument was a mixed questionnaire, applied with the leader of the strategic level, the managers of the intermediate level, the operational level of employees (administrative area) and operational level employees (industrial production sector). The data analysis was done through content analysis, from the thematic or technical categorical Bardin (2011), considering the categories of analysis drawn from the process model in GC represented by Bergeron (2003), which was used as a parameter for research, for allowing the identification of KM practices and information management practices, this part of the KM process. The results of the analysis indicate the existing shares in the company and the blanks in each step of the process. As for the management practices of knowledge, was identified the need to implement a Training, Development & Corporate Education Programme (TD&E) for the development of individual skills of employees. With respect to information management practices, was identified the importance and the need for a database of individual and organizational skills to promote the sharing of tacit knowledge among employees, as well as improving internal communication and means available for retention knowledge at the operational level/production. In relation to information technology and communication to support the process, was perceived the need for greater use of the tools and workflow CMS and different technologies EDM in order to contribute to improving the quality of information and the affection of the mechanisms storage and access to information in the corporate environment. Was identified also the need to review the information architecture in the enterprise portal. Finally, this study will support the development of policies and strategies for the implementation of a knowledge management program in Cerâmica Salema company, based on the evaluation of the initiatives already implemented and the identification of needs at each stage of the process.